2014
DOI: 10.1002/anie.201402939
|View full text |Cite
|
Sign up to set email alerts
|

Visible‐Light‐Induced Electron Transport from Small to Large Nanoparticles in Bimodal Gold Nanoparticle‐Loaded Titanium(IV) Oxide

Abstract: A key to realizing the sustainable society is to develop highly active photocatalysts for selective organic synthesis effectively using sunlight as the energy source. Recently, metal-oxide-supported gold nanoparticles (NPs) have emerged as a new type of visible-light photocatalysts driven by the excitation of localized surface plasmon resonance of Au NPs. Here we show that visible-light irradiation (λ>430 nm) of TiO2 -supported Au NPs with a bimodal size distribution (BM-Au/TiO2 ) gives rise to the long-range … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
80
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(83 citation statements)
references
References 38 publications
3
80
0
Order By: Relevance
“…The high-resolution spectrum of Au4f (Figure 2 D) exhibits two peaks at 84.0 eV (Au4f 7/2 ) and 87.6 eV (Au4f 5/2 ) that can be assigned to metallic Au. [ 38,39 ] The binding energies of 459.2 and 464.9 eV, ascribed to Ti2p 3/2 and Ti2p 1/2 , respectively, are consistent with the typical values reported for TiO 2 (Figure 2 E). [ 40 ] The asymmetric profi le of the O1s band ( Figure 2 F) indicates that more than one kind of oxygen species exist.…”
Section: Microstructuressupporting
confidence: 85%
“…The high-resolution spectrum of Au4f (Figure 2 D) exhibits two peaks at 84.0 eV (Au4f 7/2 ) and 87.6 eV (Au4f 5/2 ) that can be assigned to metallic Au. [ 38,39 ] The binding energies of 459.2 and 464.9 eV, ascribed to Ti2p 3/2 and Ti2p 1/2 , respectively, are consistent with the typical values reported for TiO 2 (Figure 2 E). [ 40 ] The asymmetric profi le of the O1s band ( Figure 2 F) indicates that more than one kind of oxygen species exist.…”
Section: Microstructuressupporting
confidence: 85%
“…The four peaks at 84.0 eV (Au 4f 7/2 ), 87.6 eV (Au 4f 5/2 ), 353.0 eV (Au 4d 3/2 ) and 334.0 eV (Au 4d 5/2 ) can be assigned to metallic Au. [26,27] In Figure 3c, the binding energies of 458.9 eV and 464.5 eV are consistent with the typical values reported for Ti 2p 3/2 and Ti 2p 1/2 , respectively. [28] In Figure 3d, the asymmetric profile of O 1s band indicates that two kinds of oxygen species exist in the system.…”
Section: Resultssupporting
confidence: 88%
“…We have reported that Au/TiO 2 with a bimodal size distribution of Au nanoparticles exhibits a high level of activity for the one-step synthesis of azobenzenes from nitrobenzenes with high yield and selectivity because of the electron transport from small Au nanoparticles to large ones. 20 be frequently the rate-determining step in the photocatalytic reactions. In the preceding work, 23 we have found that the Au/mp-TiO 2 | Pt shows the highest photocatalytic activity among Au/mp-TiO 2 on various conducting substrates.…”
Section: (A) (B)mentioning
confidence: 99%
“…In the preceding work, 23 we have found that the Au/mp-TiO 2 | Pt shows the highest photocatalytic activity among Au/mp-TiO 2 on various conducting substrates. 23 Regardless of the high cost, Pt is usually used as the cathode of fuel cells due to 20 its excellent electrocatalyst for oxygen reduction reaction (ORR). 24 The application of the large-scale fuel cells needs the development of Pt-alternative materials with high electrocatalytic activity for ORR, low cost, and earth abundance.…”
Section: (A) (B)mentioning
confidence: 99%
See 1 more Smart Citation